2017
DOI: 10.5020/18061230.2017.6688
|View full text |Cite
|
Sign up to set email alerts
|

Caracterização dos usuários e do padrão de uso das academias ao ar livre

Abstract: Este artigo publicado em acesso aberto (Open Access) sob a licença Creative Commons, que permite uso, distribuição e reprodução em qualquer meio, sem restrições, desde que o trabalho seja corretamente citado. CARACTERIZAÇÃO DOS USUÁRIOS E DO PADRÃO DE USO DAS ACADEMIAS AO AR LIVRECharacterization of users and usage pattern of outdoor fitness equipment

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 12 publications
0
9
0
2
Order By: Relevance
“…Arrival time to an OG from home is variable. In Ibiapina et al (2017) study, most users (63%) take up to 10 minutes to reach the OG but, in Iepsen & Silva (2015) study most users take more than 30 minutes, although 71% of users find it easy to walk from home to the OG. Attending to Mora (2012) and Mora et al (2017) study, in some cases, a 64% of the households found an OG within 500m.…”
Section: Barriers and Disadvantages For Usage An Ogmentioning
confidence: 90%
See 4 more Smart Citations
“…Arrival time to an OG from home is variable. In Ibiapina et al (2017) study, most users (63%) take up to 10 minutes to reach the OG but, in Iepsen & Silva (2015) study most users take more than 30 minutes, although 71% of users find it easy to walk from home to the OG. Attending to Mora (2012) and Mora et al (2017) study, in some cases, a 64% of the households found an OG within 500m.…”
Section: Barriers and Disadvantages For Usage An Ogmentioning
confidence: 90%
“…The equipment appears to be safe for users (Chow, 2013;Pinheiro & Coelho Filho, 2017;Silva et al 2016). In OGs, the 49.4% of users do not use any piece and the main reasons for not using some piece of equipment in the OGs was pain, they do not like it and non-anatomical machines (Ibiapina et al, 2017). About 31% of participants reported not knowing how to use OGs devices and 47.9% reported not controlling the use of equipment, and always using the same devices; 16% reported feeling discomfort during use.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations